2009
DOI: 10.1016/j.yexcr.2009.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic analysis of apoptosis using cyanine SYTO probes: From classical to microfluidic cytometry

Abstract: Cell death is a stochastic process, often initiated and/or executed in a multi-pathway/multi-organelle fashion. Therefore, high-throughput single-cell analysis platforms are required to provide detailed characterization of kinetics and mechanisms of cell death in heterogeneous cell populations. However, there is still a largely unmet need for inert fluorescent probes, suitable for prolonged kinetic studies. Here, we compare the use of innovative adaptation of unsymmetrical SYTO dyes for dynamic real-time analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
97
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 49 publications
(100 citation statements)
references
References 19 publications
1
97
0
2
Order By: Relevance
“…More recently the use of SYTO16 and viability dyes has allowed the discrimination of apoptosis and oncosis in that no reduction in SYTO16 was observed in cells undergoing oncosis compared to that observed in cells undergoing apoptosis (7). In another advance, propidium iodide has been used in a real-time image analysis study of apoptosis from the start of the induction process and continuously over a 24 h period (27)(28)(29). In this approach adherent cells were preloaded with Hoechst and grown in culture with a low concentration of PI (0.25 lg/ml) and then exposed to STS for 24 h with images taken every 15 min in a real-time manner (27).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently the use of SYTO16 and viability dyes has allowed the discrimination of apoptosis and oncosis in that no reduction in SYTO16 was observed in cells undergoing oncosis compared to that observed in cells undergoing apoptosis (7). In another advance, propidium iodide has been used in a real-time image analysis study of apoptosis from the start of the induction process and continuously over a 24 h period (27)(28)(29). In this approach adherent cells were preloaded with Hoechst and grown in culture with a low concentration of PI (0.25 lg/ml) and then exposed to STS for 24 h with images taken every 15 min in a real-time manner (27).…”
Section: Discussionmentioning
confidence: 99%
“…Thus the measurement of mitochondrial membrane and plasma membrane potentials in real-time affords a rapid easy method to distinguish oncosis and apoptosis at the induction stage of these two different necrobiological processes. This approach to study oncosis could used in conjunction with that employed to study apoptosis in real-time and SYTO16 and thus enable differentiation between the induction of oncosis and apoptosis in vitro and potentially ex vivo (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This methodology, however, is slowly gaining appreciation as an easy to perform, live-cell assay (68). Importantly, we have recently showed that cyanine SYTO dyes represent a promising class of inert probes that do not adversely affect normal cellular physiology (9). When preloaded or continuously present in medium, SYTO do not interfere with cell viability, and their intracellular retention permits straightforward and kinetic analysis of investigational drug/compound cytotoxicity (9).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, we have recently showed that cyanine SYTO dyes represent a promising class of inert probes that do not adversely affect normal cellular physiology (9). When preloaded or continuously present in medium, SYTO do not interfere with cell viability, and their intracellular retention permits straightforward and kinetic analysis of investigational drug/compound cytotoxicity (9). Reduction of sample processing achieved with these protocols is important for preservation of fragile apoptotic cells.…”
Section: Introductionmentioning
confidence: 99%